The aberrant overexpression of vimentin is linked to a more aggressive status in tumours of the gastrointestinal tract - Brzozowa, Marlena; Wyrobiec, Grzegorz; Kołodziej, Izabela; Sitarski, Mateusz; Matysiak, Natalia; Reichman-Warmusz, Edyta; Żaba, Małgorzata; Wojnicz, Romuald (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Vimentin is an intermediate filament protein normally expressed in cells of mesenchymal origin, e.g. myofibroblasts, chondrocytes, macrophages, and endothelial cells. The expression of vimentin, which has been thought of as the main mesenchymal marker, is also detected in tumour tissue. In tumours of the gastrointestinal tract vimentin expression is usually correlated with advanced stage of tumour, lymph node metastasis, and patient survival.